Pelatihan Jarimatika Perkalian Sembilan di SD Calengka Desa Bumiwangi - Rapida, Ida; Wandari, Arsya Dwi; Hayat, Nahrul (Ma'soem University, 2024)
Community service (PKM) with the title of Jarimatika Training for Nine Multiplications was motivated by the assumption of some students that mathematics, especially multiplication, is a scary subject because it is difficult to understand. Actually, there are many fun learning methods where students find it easy to understand multiplication. One of them is by using the jarimatika method where the fingers are used as a calculation tool. The purpose of this training is to make multiplication calculations fun, where students learn to count while playing their fingers as if they were playing a game. The target subjects of the PKM activity were fourth grade students at Calengka Elementary School, Bumiwangi Village, Ciparay District, Bandung Regency. The method used was PAR (Participatory Action Research) which was divided into five stages, namely: to know; b. to understand; c. to plan; d. to act; e. to change. The results of the activity showed that through this training, students' ability to perform calculations by multiplying nine became faster and more fun.